Dissection of entropy production for the free convection of NEPCMs-filled porous wavy enclosure subject to volumetric heat source/sink - Afshar, S.R.; Mishra, S.R.; Dogonchi, A. Sattar; Karimi, Nader; Chamkha, Ali J.; Abulkhair, Hani (Journal of the Taiwan Institute of Chemical Engineers, 2021)
•Free convection of NEPCMs along with entropy generation in an enclosure is dissected.•The porous wavy enclosure may well be subject to a volumetric heat source/sink.•The structure of the wavy part varies based on its undulation number and amplitude.•The finite element method may well be applied to solve the governing equations. The exploration of natural convection which is one the substantial types of convective heat transmission in various applications for instance heat exchangers and geothermal systems along with nanofluids (Nanofluids have greater thermal conductivity in comparison to the conventional fluids) engrossed all researchers’ attention. This study is dedicated to the inspection of the free convection of nanofluid as well as entropy generation inside a porous cavity loaded with nano-encapsulated phase change materials (NEPCMs). The wavy bottom section of the enclosure may be subject to a constant heat flux due to the transmitted sunlight comes from a parabolic trough solar collector. The volumetric heat source/sink is comprised in the governing equation. The robust finite element method (FEM) is deployed to handle the transformed governing equations. The numerical simulation of the streamlines and isotherms associated with velocity distribution for diverse factors are displayed. Further, the significant behavior of the contributing parameters on the Nusselt and Bejan numbers are represented. The results demonstrate that the various profiles of wavy bottom section could affect the heat transmission features as well as fluid flow remarkably. Furthermore, it is noteworthy that all the profiles of entropy enhance with increasing the amplitude with respect to the increasing undulation number for the existence of various Rayleigh number. [Display omitted]